A Validation of the Health and Social Costs of Asthma Using Questionnaire Data: IJPDS (2017) Issue 1, Vol 1:164, Proceedings of the IPDLN Conference (August 2016) - Brookman, Alison; Davies, Gwyneth (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Cost-burden analyses usually lack a wider societal perspective. Through the creation of a robust resource use measure (RUM), data gaps on societal costs will be addressed, allowing more accurate estimates of the cost burden of asthma in the UK. Approach A systematic review, applying an established checklist and data extraction tool, will identify and evaluate those existing methods and measures of generating resource use data. These data, incorporated with focus group data, will inform the design of a new RUM. To be distributed to 2000 participants, randomly selected from GP practices (Swansea & Edinburgh), the Swansea data will be linked and validated with their record held in SAIL (Secure Anonymised Information Linkage). A nested cost burden analysis will be applied, generating an estimate of relevant societal costs. Preliminary results A preliminary search of the ‘PubMED’ database generated 181 papers that met the inclusion criteria. Initial analysis shows that a societal perspective is usually lacking from RUMs. A critical appraisal of these measures has identified significant variance in both the quality and content of the questionnaires. Focus groups highlighted a number of cost elements that are not, as yet, discussed in the literature. Conclusion Societal cost factors are not adequately captured within existing tools, our findings will inform the development of a new RUM which will be piloted and validated according to best practice guidelines. Capturing the societal costs of asthma will allow more accurate estimates of the total costs of asthma in the UK.